Medications influencing the risk of fall-related injuries in older adults: case–control and case-crossover design studies - Yu-Seon Jung; David Suh; Eunyoung Kim; Hee-Deok Park; Dong-Churl Suh; Sun-Young Jung (BMC Geriatrics, 2023)
Abstract Background Medications influencing the risk of fall-related injuries (FRIs) in older adults have been inconsistent in previous guidelines. This study employed case–control design to assess the association between FRIs and medications, and an additional case-crossover design was conducted to examine the consistency of the associations and the transient effects of the medications on FRIs. Methods This study was conducted using a national claims database (2002–2015) in Korea. Older adults (≥ 65 years) who had their first FRI between 2007 and 2015 were matched with non-cases in 1:2 ratio. Drug exposure was examined for 60 days prior to the date of the first FRI (index date) in the case–control design. The hazard period (1–60 days) and two control periods (121–180 and 181–240 days prior to the index date) were investigated in the case-crossover design. The risk of FRIs with 32 medications was examined using conditional logistic regression after adjusting for other medications that were significant in the univariate analysis. In the case-crossover study, the same conditional model was applied. Results In the case–control design, the five medications associated with the highest risk of FRIs were muscle relaxants (adjusted odd ratio(AOR) = 1.35, 95% confidence interval (CI) = 1.31–1.39), anti-Parkinson agents (AOR = 1.30, 95%CI = 1.19–1.40), opioids (AOR = 1.23, 95%CI = 1.19–1.27), antiepileptics (AOR = 1.19, 95%CI = 1.12–1.26), and antipsychotics (AOR = 1.16, 95%CI = 1.06–1.27). In the case-crossover design, the five medications associated with the highest risk of FRIs were angiotensin II antagonists (AOR = 1.87, 95%CI = 1.77–1.97), antipsychotics (AOR = 1.63, 95%CI = 1.42–1.83), anti-Parkinson agents (AOR = 1.58, 95%CI = 1.32–1.85), muscle relaxants (AOR = 1.42, 95%CI = 1.35–1.48), and opioids (AOR = 1.35, 95%CI = 1.30–1.39). Conclusions Anti-Parkinson agents, opioids, antiepileptics, antipsychotics, antidepressants, hypnotics and sedatives, anxiolytics, muscle relaxants, and NSAIDs/antirheumatic agents increased the risk of FRIs in both designs among older adults. Medications with a significant risk only in the case-crossover analysis, such as antithrombotic agents, calcium channel blockers, angiotensin II antagonists, lipid modifying agents, and benign prostatic hypertrophy agents, may have transient effects on FRIs at the time of initiation. Corticosteroids, which were only associated with risk of FRIs in the case–control analysis, had more of cumulative than transient effects on FRIs.